2017
DOI: 10.1016/j.jgeb.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA genetic variations among four horse populations in Egypt

Abstract: Horses are one of the early domesticated animals in the world that changed societies and civilizations on a continent-wide scale. Due to the rare information about the genetic characterization of different horse populations in Egypt, this study aimed to identify the genetic biodiversity and relationships between four horse populations reared in Egypt. Genomic DNA was extracted and mtDNA region was amplified using polymerase chain reaction (PCR). The alignment of 384-bp amplified fragments showed the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…All these haplogroups were considered as of European origin by [11] except for haplogroup Q, which has a more Asian or Middle Eastern distribution and is present, for example, in the Arabian horse. Mitochondrial DNA diversity in the Finnhorses ( = 0.022 and = 0.979) is relatively similar to that detected in many other horse breeds [4143]. In the domestic horse, it has been suggested that the large number of haplogroups and haplotypes spread over wide geographic regions results from a large number of mares having been incorporated into the domestic horse population [11, 12, 44].…”
Section: Discussionsupporting
confidence: 54%
“…All these haplogroups were considered as of European origin by [11] except for haplogroup Q, which has a more Asian or Middle Eastern distribution and is present, for example, in the Arabian horse. Mitochondrial DNA diversity in the Finnhorses ( = 0.022 and = 0.979) is relatively similar to that detected in many other horse breeds [4143]. In the domestic horse, it has been suggested that the large number of haplogroups and haplotypes spread over wide geographic regions results from a large number of mares having been incorporated into the domestic horse population [11, 12, 44].…”
Section: Discussionsupporting
confidence: 54%
“…The haplotype diversity of Kabardian (0.980) is similar to that of the additional investigated Asian horses or higher. That also applies to comparison with other breeds like Arabian (0.784 and 0.962), Thoroughbred (0.883 and 0.942), Kazakh (0.977), Chinese (0.978 and 0.989) as well as Brazilian (varying from 0.200 to 0.944) horses (Zhang et al, 2012;Ianella et al, 2017;Othman et al, 2017). However, the Kabardian horse has a huge genetic variability in its maternal lineages representing a diverse origin and a longstanding history, which is in agreement with recently published microsatellite analysis (Duduev et al, 2014).…”
Section: Phylogenetic Analysismentioning
confidence: 92%
“…Sequenced fragments of the horse MSTN gene were assembled into one sequence of 463 bp that resulted 100% identical with that was in the existing data in GenBank derived from Equus caballus compare with Although some studies has mentioned about the mt-DNA genetic variations in horses based on its breeds, countries and regions [12] [13] [14], there is still rare information about the role of MSTN gene in Sandalwood horse. Up to now, the selection is just based on its morphology that has limitations.…”
Section: Resultsmentioning
confidence: 99%